1982
DOI: 10.1121/1.388443
|View full text |Cite
|
Sign up to set email alerts
|

Effects of masker duration in pure-tone forward masking

Abstract: The masking of one tone by a preceding tone (forward masking) was studied as a function of the duration of the masker. In general it was found that forward masking increased with increasing masker duration for the range of durations used (35 to 500 msec). The functions relating masked probe threshold in decibels to the logarithm of masker duration were well described by straight lines. The rate of growth of forward masking as a function of masker duration was greatest for relatively high masker levels and freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 0 publications
2
31
1
Order By: Relevance
“…Aftereffects may occur for various low-level stimulus properties and in various sensory modalities as evidenced by previous research. Exposure to sounds was shown to induce temporary changes in the ability to discriminate intensities (Zeng et al, 1991;Zeng and Turner, 1992;Carlyon and Beveridge, 1993;Plack et al, 1995;Zeng and Shannon, 1995;Plack, 1996;Oberfeld, 2007Oberfeld, , 2008 or to detect target sounds in noise (Penner, 1974;Kidd and Feth, 1982;Viemeister and Bacon, 1982;Wright et al, 1993). Furthermore, amplitude-or frequency-modulations (AMs or FMs, respectively) of preceding sounds were found to temporarily increase detection thresholds for AMs or FMs of subsequent sounds (Kay and Matthews, 1972;Kay, 1973, 1974;Regan and Tansley, 1979;Tansley and Suffield, 1983;Moody et al, 1984;Viemeister, 2003, 2005).…”
Section: Introductionmentioning
confidence: 93%
“…Aftereffects may occur for various low-level stimulus properties and in various sensory modalities as evidenced by previous research. Exposure to sounds was shown to induce temporary changes in the ability to discriminate intensities (Zeng et al, 1991;Zeng and Turner, 1992;Carlyon and Beveridge, 1993;Plack et al, 1995;Zeng and Shannon, 1995;Plack, 1996;Oberfeld, 2007Oberfeld, , 2008 or to detect target sounds in noise (Penner, 1974;Kidd and Feth, 1982;Viemeister and Bacon, 1982;Wright et al, 1993). Furthermore, amplitude-or frequency-modulations (AMs or FMs, respectively) of preceding sounds were found to temporarily increase detection thresholds for AMs or FMs of subsequent sounds (Kay and Matthews, 1972;Kay, 1973, 1974;Regan and Tansley, 1979;Tansley and Suffield, 1983;Moody et al, 1984;Viemeister, 2003, 2005).…”
Section: Introductionmentioning
confidence: 93%
“…Several authors have suggested that psychophysical forward masking is a direct consequence of this process (Duifhuis, 1973;Smith, 1977Smith, , 1979Jesteadt et al, 1982;Kidd and Feth, 1982), and it is common to describe a poststimulation reduction in neural activity as forward masking (Harris and Dallos, 1979;Shore, 1995;Brosch and Schreiner, 1997). However, a poststimulation reduction in neural activity does not necessarily imply masking.…”
Section: Forward Masking and Neural Adaptationmentioning
confidence: 99%
“…Neural adaptation has also been proposed as a mechanism of forward masking (Kidd and Feth, 1982). Neural adaptation refers to the decrease in a nerve fiber's response to a steady-state stimulus over the course of stimulation.…”
Section: Introductionmentioning
confidence: 99%